Maximal productivity rate of threading machine operations - Ryspek Usubamatov; Darina Kurganova; Sarken Kapayeva (International Journal of Mathematics for Industry)
The quality of products in manufacturing engineering depends first of all on the machining processes. One of the crucial economic components of the production processes is the metal-cutting machining technologies that form the quality of manufactured objects. The physics of metal-cutting technologies is complex and cannot be described by one mathematical model because of different natures. Researchers derived an empirical formula of their tool life that describes the properties of the metal-cutting tools depending on many mechanical factors mentioned above. Engineers investigated and worked the metal-cutting regimes for manufacturing processes that comprise recommendations for the tool life. The components of the tool life are obtained by the practical tests at the research laboratories that give the approximated results. Practice shows the recommendations of the handbooks for metal-cutting regimes are not always optimal for manufacturing processes. The machine tools’ work in the manufacturing environment differs from the research laboratories. This work considers the analytical optimization of the cutting speed for the threading machine tool by the criterion of its maximal productivity rate.